Educational process in palliative care and the overhaul of thinking - Knopp de Carvalho, Karen; Lerch Lunardi, Valéria; Arruda da Silva, Priscila; Schäfer Vasques, Tânia Cristina; Coelho Amestoy, Simone (Investigación y Educación en Enfermería, 2017)
Objective. To know the contributions of the educational process in Palliative Care during the undergraduate level for the professional action of nurses in the care of patients at the end of life. Methods. This is a qualitative research, with discursive thematic analysis, based on Morin’s theory of complexity. It was attended by seven newly-trained nurses and six nursing teachers from a Nursing Undergraduate Course. Results. It has found disruptions and the development of new ways of thinking and caring for patients at the end of life, highlighting that these patients should be treated with therapies to mitigate their signs and symptoms until death, focusing on quality of life; moreover, their psychosocial and spiritual aspects should be appreciated. Conclusion. The educational process in palliative care seems to be essential for nurses, as a way of organizing and systematizing patient care. It becomes indispensable that nursing programs also provide the students with the development of the awareness of the complexity of the human being and its relationship with the multiple biopsychosocial and spiritual aspects. How to cite this article: Carvalho KK, Lunardi VL, Silva PA, Vasques TCS, Amestoy SC. Educational process in palliative care and the overhaul of thinking. Invest. Educ. Enferm. 2017; 35(1):